Initial participation as a predictor for continuous participation in population-based colorectal cancer screening. (September 2018) - Saraste, Deborah; Öhman, Daniel J; Sventelius, Marika; Elfström, K Miriam; Blom, Johannes; Törnberg, Sven
Objectives: To assess patterns and probabilities of participation in multiple rounds of colorectal cancer screening. Methods: All individuals who were invited to participate in population-based colorectal cancer screening in the Stockholm-Gotland region in Sweden between 1 January 2008 and 30 September 2015 were included in the study. Guaiac-based faecal occult blood testing was used. All individuals invited to the three first consecutive screening rounds were included in the analysis. Results: There were 346, 168 individuals eligible for invitation to screening. The average participation rate during the follow-up period was 60%. Eligible individuals could be invited 1–4 times, depending on age at first invitation. Of 48, 959 individuals invited to the three first consecutive rounds of screening, 71% participated at least once, and 50% participated in all three rounds. Participation at first invitation was a predictor for participation in subsequent rounds, and the likelihood of continuous participation following participation in the first round was 84%. Of those who attended the first and second rounds, 93% also participated in the third round. Similar patterns of consistency were seen among non-participants. For individuals not participating in the first screening round, the likelihood of consistent non-participation was 71. Conclusions: Participation in the first round of screening is a strong predictor for participation in subsequent rounds. Therefore, reducing barriers for initial participation is a key for achieving consistent participation over several rounds in organized colorectal cancer screening programmes.